Study of 448 cases of melanoma in situ in two hospitals in Rio de Janeiro - Luciana Pantaleão; Mayra Carrijo Rochael (Sociedade Brasileira de Dermatologia, 2017)
Abstract: The diagnosis of cutaneous melanoma in situ, considered to have excellent prognosis, has been increasingly frequent, with rare isolated reports of cutaneous melanoma in situ presenting recurrence, metastasis, and death. No specific study is found in the literature about these lesions of unexpected behavior. We describe the demographic and histopathological findings of 448 cases of cutaneous melanoma in situ in 369 patients, emphasizing the prognostic criteria of those with unfavorable outcomes, corresponding to 9 cases in which regression had no significant role. Adnexotropism was found in 44.5% of cases. The study of early lesions would allow clinicians to have a better understanding of the evolutionary processes of the disease.